2020
DOI: 10.1186/s12890-020-01362-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of Japanese patients with exacerbations of chronic obstructive pulmonary disease

Abstract: Background Exacerbations are critical events in chronic pulmonary obstructive disease (COPD). The frequency of COPD exacerbations is associated with the prognosis, including mortality, but no useful biomarker has been established. Methods The present retrospective study investigated 481 COPD patients. Clinical features in the stable period were compared between patients who experienced severe exacerbation (n = 88, 18.3%) and those who never experienced severe exacerbation (n = 393, 81.7%). In the patients who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…23 From this perspective, respiratory events such as LRTIs may be considered as markers of COPD risk and poorer prognosis. However, it should be noted that other potential confounders such as smoking, exposure to air pollutants or eosinophil count 24 could not be accounted for in our models because data on them are not collected in the JMDC database.…”
Section: Discussionmentioning
confidence: 99%
“…23 From this perspective, respiratory events such as LRTIs may be considered as markers of COPD risk and poorer prognosis. However, it should be noted that other potential confounders such as smoking, exposure to air pollutants or eosinophil count 24 could not be accounted for in our models because data on them are not collected in the JMDC database.…”
Section: Discussionmentioning
confidence: 99%
“…Most cohort studies have continued to pay attention to the association between BEC and AECOPD [21], but they have also provided inconsistent results. While some have reported a positive association between BEC with COPD exacerbation frequency [18,[44][45][46], other cohort studies have reported that there was no evidence of such an association (Table 4) [20,41,43,47]. Although most previous studies were designed to statistically compare the frequency of AECOPD between groups, the period from baseline to the first exacerbation is intended to be analysed using the univariate Cox proportional hazards model.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, exercise can exacerbate the phenomena [ 113 ] that might contribute to avoidance of moderate or vigorous physical activity and increase sedentary behavior. Even worse, the sequence of behavior induces a negative feedback cycle leading to poor outcomes for COPD patients, because increasing sedentary time with a reduction in physical activity contributes to skeletal muscle atrophy, especially in antigravity muscles such as the erector spinae muscles and thigh muscles, causing weight loss and decreased exercise capacity [ 59 , 66 , 67 , 114 ]. Consequently, the symptoms of dyspnea and shortness of breath are induced at a low intensity of physical activity, and patients try to avoid movement along with progression of muscle atrophy.…”
Section: Clinical Impact Of Sedentary Behavior In Patients With Chron...mentioning
confidence: 99%
“…These data showed that sedentary behavior time was reduced because of improvement of decreased inspiratory capacity, which contributes to shortness of breath and dyspnea, by dual bronchodilator therapy. Recently, inhaled corticosteroid therapy was also found to be effective for patients with COPD, especially in those with frequent exacerbations with elevation of blood eosinophil levels [ 114 , 119 ]. We do not know the impact of inhaled corticosteroid therapy on sedentary behavior in patients with COPD, and further trials are needed to clarify its efficacy.…”
Section: Possible Interventions Focused On Physical Activity Especial...mentioning
confidence: 99%